Pedagogical And Psychological Support For The Introduction Of The Home Education System For Students With Disabilities - Malika Ergasheva (Penerbit Jurnal Indonesia, 2024)
This article explores the critical need for both pedagogical and psychological support when introducing home education for students with disabilities. It emphasizes the importance of individualized learning plans (IEPs) and adapted teaching methods to accommodate students' diverse needs. Additionally, the article highlights the role of emotional and social support, particularly through the involvement of educators, psychologists, and parents. It addresses the challenges of resource limitations, parental burnout, and social isolation, offering practical solutions to enhance the home education experience. The collaborative effort between educators and psychologists ensures that students receive both academic and emotional guidance, promoting a well-rounded and inclusive learning environment.